A Comparative Assessment of Chromium–Boron Hardfacing Using SMAW and FCAW Techniques - Chowda Reddy C.; K. M. Kenchi Reddy; C. T. Jayadeva; Ramesh Kumar S. C.; R. Vara Prasad Kaviti; Abhijit Bhowmik; Chander Prakash (The Scientific World Journal)
This research paper investigates the effectiveness of shielded metal arc welding (SMAW) and flux-cored arc welding (FCAW) on mild steel substrates for chromium–boron hardfacing. Chromium–boron alloys are hard-wearing and corrosion-resistant materials used in industries where wear resistance is critical. The study aims to identify the best welding technique for increasing surface hardness and wear resistance. Standard test specimens were chosen and deposited using SMAW and FCAW processes. SMAW uses an electrode covered with flux, which turns into a sticky state when heated, while FCAW uses a core wire fabricated from flux, which generates a shielded gas upon melting. The effectiveness of each welding technique is assessed based on deposition efficiency, dilution rate, microstructure, hardness distribution, and wear resistance. This research helps industries choose the most efficient material and method for improving wear and corrosion resistance in applications like mining, construction, agriculture, and manufacturing. On average, FCAW offers a 1.67% improvement in hardness and 28.12% improvement in mass loss reduction when compared to SMAW.